2012
DOI: 10.1016/j.socscimed.2011.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Waiting times and socioeconomic status: Evidence from England

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link ABSTRACTWaiting times for elective surgery are often referred to as an equitable rationing mechanism in publicly-funded healthcare systems providing access to care not on the basis on willingness to pay or socioeconomic status. This study uses patient level administrative data from the Hospital Episode Statistics database in England to investigate whether patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
113
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 24 publications
7
113
0
5
Order By: Relevance
“…This in turn would result in a larger volume of services being allocated to such patients every year as compared with socioeconomically disadvantaged patients who face higher costs in exercising choice and hence are more likely to stay on the waiting list of their local hospital provider. In contrast, advocates of reform claim that this sort of two tier system was already in place before the introduction of competition, with socioeconomically advantaged individuals travelling longer distances (Propper et al 2007) in order to obtain their treatment in hospitals with shorter waiting times (Laudicella et al 2012, Cooper et al 2009. The introduction of choice and competition would then benefit socioeconomically disadvantaged patients by making it easier for them to choose hospitals with shorter waiting times (Dixon and Le Grand, 2006).…”
Section: Choice and Waiting Timesmentioning
confidence: 99%
“…This in turn would result in a larger volume of services being allocated to such patients every year as compared with socioeconomically disadvantaged patients who face higher costs in exercising choice and hence are more likely to stay on the waiting list of their local hospital provider. In contrast, advocates of reform claim that this sort of two tier system was already in place before the introduction of competition, with socioeconomically advantaged individuals travelling longer distances (Propper et al 2007) in order to obtain their treatment in hospitals with shorter waiting times (Laudicella et al 2012, Cooper et al 2009. The introduction of choice and competition would then benefit socioeconomically disadvantaged patients by making it easier for them to choose hospitals with shorter waiting times (Dixon and Le Grand, 2006).…”
Section: Choice and Waiting Timesmentioning
confidence: 99%
“…Concretely, if GDP were increased by 1%, the waiting list would decrease byapproximately 0.91%, ceteris paribus. Although several authors have found a positive relationship between income and waiting times (Laudicella et al, 2012 or Siciliani andVerzulli, 2009), these results may indicate a positive relationship between more income and better health which has been amply discussed in the literature. For example, Marmot et al (1978), Lantz et al (2007), Lantz and Pritchard (2010), Lee et al (1995), Rose (2001), Case and Deaton (2005), Galama and Kipperluis (2015) amongst others, find that income and social class are, in general, good predictors of morbidity and mortality given that lower social classes tend to lead less healthy lifestyles with worse behaviours than superior social classes.…”
Section: Resultsmentioning
confidence: 85%
“…99,100 However, there is evidence to suggest that there remains significant socioeconomic inequalities in waiting time. For instance, Laudicella et al 101 found that elective hip replacement patients in the poorest two socioeconomic quintiles wait about 7% longer than patients in the least deprived quintile across England. In another study, Moscelli et al…”
Section: Hospital Waiting Timementioning
confidence: 99%